Monitoring of Insect Species Richness and Abundance in Sudan Semi-arid Ecosystem (Case study: Khartoum State/Sudan) - A. Abdellatif, Maha; Gadir M. Abdellah, Abdel; H. Abdalla, Ishtiag; I. Ahmed Safi, Ahmed; E. Eltayeb, Randa (International Journal of Entomology, 2025)
Sudan's ecological landscape is characterized by various zones, including deserts, semi-deserts, and savannas, which host a diverse array of forests, rangelands, and numerous plant and animal species. However, the sustainable management of these resources is becoming increasingly challenging due to human activities and the impacts of climate change. This article presents the results of a research project focused on monitoring and documenting biodiversity in Sudan's semi-arid regions, particularly emphasizing insect diversity. Insects are vital for maintaining ecosystem health through processes such as nutrient cycling, decomposition, pollination, and acting as natural predators to pests. Field surveys were conducted across three Sudanese states—North Kordofan, Gezira, and Khartoum—to assess the diversity of flora and fauna. Specifically, El Rawakeeb semi-arid land in Khartoum state was investigated, which comprised three sites with varying soil elevations: a hilly site at 420 meters above sea level, a flat site at 416 meters, and a valley site at 411 meters. Researchers utilized direct collection methods and butterfly nets to gather insect specimens, which were subsequently preserved and identified for further analysis. Diversity indices, including Simpson’s Diversity Index, Shannon-Wiener Index, and Margalef Richness Index, were computed to compare the biodiversity of these sites, along with metrics for evenness and species richness. Permanova analysis was carried out for insect variation between the study sites. A total of 1541 insect specimens were gathered from El Rawakeeb, encompassing 34 species distributed across 21 families and 9 orders. The order Lepidoptera exhibited the greatest number of species (35.29%), followed by Coleoptera (20.59%). The orders Neuroptera, Orthoptera and Thysanoptera recorded the fewest species (2.94% each). From the hilly site, 514 insect specimens were collected, representing 9 orders, among which Hymenoptera included 4 species, while Lepidoptera had 3 species, and Odonata, Orthoptera, and Thysanoptera each had 1 species. The highest individual counts were recorded for Copriniklobe (dung beetle), Dacus longistylus (fruit fly), Camponotussp. (carpenter ant), and Anax ephippiger (dragonfly). In a flat site, 484 insect specimens were collected, classified into 15 species, 12 families, and 7 orders. The highest individual counts were noted in four species: Onthophagusnuba (dung beetle), Dacus longistylus (fruit fly), Camponotussp. (carpenter ant), and Anax ephippiger (dragonfly). In a valley site, 543 insect specimens were collected, categorized into 17 species, 16 families, and 9 orders. Insect Diversity in three research sites. Simpson's Diversity Index revealed varying levels of insect diversity across the three sites. The valley site exhibited the highest diversity level with an index score of 0.857, followed by the flat site at 0.826, and the hilly site at 0.819. The Shannon diversity index of 2.22 indicated the highest diversity among the three sites, suggesting a relatively diverse insect community. The relative abundance of insects was greatest in the valley site at 35.24%, followed by the hilly site at 33.35%, and the flat site at 31.41%. The Margalef Richness Index indicated a moderate level of richness in the insects collected from the three locations. Certain insect species were found in some sites but were absent in others. The PERMANOVA revealed notable variations among the three study sites (F = 2.24, p-value = 0.035).
Keywords: insect biodiversity; species richness; abundance; semi-arid ecosystems; Sudan; diversity indices